Respuesta :

Answer:

Equation: y = -2x

Solution: y = 12

Step-by-step explanation:

y varies directly as x, can be expressed by the equation, y = kx. Where, k = constant of proportionality.

Given that when x = 2, y = -4, to find the value of k, plug in the values of x and y into y = kx.

Thus:

-4 = k(2)

Divide both sides by 2

-4/2 = k

k = -2

To write the equation for the information given, substitute k = -2 into y = kx.

✔️Equation: y = -2x

✔️When x = -6,

y = -2x

Plug in the value of x

y = -2(-6)

y = 12

ACCESS MORE